2001
DOI: 10.1034/j.1600-051x.2001.028003255.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chewing sugar‐free gum on plaque regrowth at smooth and occlusal surfaces

Abstract: Chewing gum can reduce plaque accumulation at sites of predilection for caries but has little or no effect at sites of predilection for gingivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
2
14
0
1
Order By: Relevance
“…Sugar-free gum was also shown to reduce occlusal plaque regrowth to a considerable degree (approximately 44%), whereas no significant effect on smooth surface plaque was demonstrated. 10 Sugar-free gums containing additives, such as enzymes, abrasives and divalent metal ions, might exhibit an improved antiplaque activity, in a way that such products could be considered useful adjuncts to mechanical oral hygiene. Little research has been conducted on the antiplaque activity of abrasive-and zinc-containing gum products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sugar-free gum was also shown to reduce occlusal plaque regrowth to a considerable degree (approximately 44%), whereas no significant effect on smooth surface plaque was demonstrated. 10 Sugar-free gums containing additives, such as enzymes, abrasives and divalent metal ions, might exhibit an improved antiplaque activity, in a way that such products could be considered useful adjuncts to mechanical oral hygiene. Little research has been conducted on the antiplaque activity of abrasive-and zinc-containing gum products.…”
Section: Discussionmentioning
confidence: 99%
“…The 4-day plaque regrowth design that was used represents the typical design to determine the plaque inhibitory activity of different mouthrinse formulations, 13,27 while it has been also used to study the effects of chewing gum on plaque accumulation. 10,26 This design usually deals with the efficacy of a test agent on supragingival plaque regrowth after professional toothcleaning and in a short term. During the 4-day study period, toothbrushing is avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its sticky surface, the mechanical forces produced during chewing and the increase in salivary flow (with a consequent increase in clearance) remove a certain amount of plaque from the more exposed teeth surfaces (free faces and occlusal surface) 3 . This was demonstrated in a study which compared plaque rate before and after chewing sugar-free gum and reported approximately 44% less plaque after consuming chewing gum 17 . Although chewing gum can reduce plaque accumulation in predilection sites of dental caries, it has little or no effect on the predilection sites for gingivitis 17 , even though there have been reductions in the gingival index 14 .…”
Section: Mechanical Control Of Bacterial Plaquementioning
confidence: 98%
“…Continued fermentation of sugars trapped in dental plaque in conjunction with attenuated oral buffering capacity of diluted saliva seems to explain why tap water did not enhance oral pH in this trial. It is worthy to note that chewing sugar-free gums removes dental plaque from occlusal surfaces of teeth (Hanham and Addy, 2001).…”
Section: Discussionmentioning
confidence: 99%